Effects of annealing conditions on the surface morphology and crystallinity of sputtered ZnO nano films - J. Karamdel; C.F. Dee; B. Yeop Majlis (Universiti Kebangsaan Malaysia, 2011)
The effects of annealing parameters on crystallinity and surface morphology of RF sputtered zinc oxide nano films were investigated. The structure and morphology of the nano films were dependent on temperature, gas flow rate and time of annealing. The results from atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) showed smooth and uniform growth of c-axis orientation films with an average grain sizes from 10 to 30 nm. Increments of the annealing temperature from 400 to 800°C led to bigger grain size, better crystallinity and also increase of the surface roughness. Moreover, the results showed that the crystallinity was independent of the annealing time up to 40 min after starting the annealing process. Increase in the percentage of oxygen in the O/Ar (mixture of annealing gases) from 50% to 100% results in no changes in AFM results, but XRD revealed that the (100) peak intensity was decreased, the position of (002) peak was slightly shifted towards higher angle and FWHM of (002) peak was improved.